Characteristics of Injuries Sustained Under the Influence of Alcohol in a Group of Adolescents: Is it Possible to Establish a Typical Clinical Picture of an Underage Patient Who Suffered From an Injury Under the Influence of Alcohol?. Issue 2 (February 2022) - Milczarek, Olga; Kuzaj, Julia; Stanuszek, Agnieszka; Kwiatkowska, Karolina; Brzewski, Paweł; Kwiatkowski, Stanisław
Abstract : Objectives: Fractures of the limbs and craniocerebral trauma are the most common injuries in children and adolescents. Their frequency ranges widely from 32% to 85% and is the main reason for hospitalization in pediatric population. The number of injuries sustained under the influence of alcohol is increasing although the data concerning that subject is limited and usually includes both adult and teenage patients. Methods: A group of 111 adolescents (age, 9–18 years), hospitalized after traumatic brain injury with and without alcohol intoxication, was included in the study. We performed the assessment of the severity of the course of the multiorgan and craniocerebral injuries. The study was accepted by the Ethics Committee of the Jagiellonian University Medical College (no: KBET/8/B/2010). Results: The injuries of upper limbs and head and their serious consequences were observed more often in the examined group. The differences of the degree of head and neck injuries measured in the Injury Severity Score between the groups were statistically significant, although the injuries within the examined group were less often serious. There was a negative correlation between the patients' condition according to the Glasgow Coma Scale and the concentration of alcohol in their blood. No link between the patients' assessment in the Injury Severity Score and concentration of alcohol in the blood was noticed. Conclusions: Traumatic brain injury under the influence of alcohol in adolescents differs from trauma in patients who had not drunk alcohol. Similar areas of injury result in a more severe course of illness in the examined group. Abstract : Supplemental digital content is available in the text.